Evaluation of the Diagnostic Method of Urinary Nitrite - Meymandinejad, Zahra; Aliakbari, Fereshteh; Shariatpanahi, Samira; Hashemi, Reza (Archives of Men's Health, 2020)
Introduction: Nitrite test is a simple, inexpensive method for diagnosing urinary tract infections. This paper evaluates the efficiency of nitrite test in the diagnosis of urinary infections. In doing so, we analyzed patients in Khatam-ul-Anbia Hospital of Zahedan City and determined the sensitivity and specificity of this test. Material and Methods: This is a cross-sectional study involving 200 randomly selected patients with urinary infection symptoms in Khatam-ul-Anbia Hospital. Urine samples were tested for the presence of nitrite and urine culture was performed. Results: We selected 200 patients, out of which 100 had negative nitrite test and 100 had positive nitrite test. Out of 100 patients with negative nitrite test, only 4 had positive urine culture. Out of 100 patients with positive nitrite test, 98 had positive urine culture with colony count of more than 105 CFU/ml (sensitivity: 98%, specificity: 96.9%). Conclusion: As an inexpensive and easy method, nitrite test is a valuable test which can obviate the need for urine culture before treatment.